2020
DOI: 10.1186/s12872-020-01358-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high-risk coronary plaques in patients with and without metabolic syndrome and the relationship with prognosis

Abstract: Background: Metabolic syndrome (MS) is a disorder, characterized by clusters of cardiovascular risk factors such as central obesity, insulin resistance, dyslipidemia and hypertension. Patients with MS may have a higher plaque burden that increases their risk of major adverse cardiovascular events (MACEs). This study aimed to analyze the prevalence of high-risk coronary plaques in patients with and without MS by coronary computed tomography angiography (CCTA) and to investigate the relationship between MS, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Certainly, intracoronary imaging has demonstrated that plaques in MetS have a greater lipid burden compared with plaques in controls [ 31 ]. On CCTA, individuals with MetS are more likely than those without MetS to have non-calcified and high-risk plaques [ 32 , 33 ]. Beyond coronary atherosclerosis, MetS also associates with myocardial steatosis and subclinical myocardial dysfunction [ 34 ], which portend worse cardiac outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, intracoronary imaging has demonstrated that plaques in MetS have a greater lipid burden compared with plaques in controls [ 31 ]. On CCTA, individuals with MetS are more likely than those without MetS to have non-calcified and high-risk plaques [ 32 , 33 ]. Beyond coronary atherosclerosis, MetS also associates with myocardial steatosis and subclinical myocardial dysfunction [ 34 ], which portend worse cardiac outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…On CCTA, individuals with MetS are more likely than those without MetS to have non-calcified and high-risk plaques [32,33]. Beyond coronary atherosclerosis, MetS also associates with myocardial steatosis and subclinical myocardial dysfunction [34], which portend worse cardiac outcomes.…”
Section: Mets and Coronary Atherosclerosismentioning
confidence: 99%
“…A VIF larger than 4.0 was considered an indication of severe multicollinearity in the regression model. 34 For the sensitivity analysis of the multivariable logistic regression, we also calculated a model with only including significant risk factors in the univariable analysis as covariates. All the statistical analyses were performed by IBM SPSS for Windows (V.20.0, SPSS, Chicago, IL, USA) and R software V.3.6.3.…”
Section: Methodsmentioning
confidence: 99%
“…Raised hsCRP levels have been consistently associated with coronary heart disease and MetS. [43][44][45] In a study by Yang et al, 44 there was a higher level of hsCRP in the MetS group. This finding suggests a higher level of inflammation and oxidative stress in these patients, which creates a conducive pathophysiological environment for high-risk plaque development.…”
Section: Discussionmentioning
confidence: 99%